1989
DOI: 10.1093/geronj/44.4.m118
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Vestibular and Somatosensory Contributions to Balance Control in the Older Adult

Abstract: Age- and pathology-related changes in the relative contributions of visual and somatosensory inputs to dynamic balance control were evaluated. Young adults (mean age = 25, SD = 4) were compared to older adults (mean age = 68, SD = 5). Electromyographic responses were collected when subjects' balance was perturbed on a movable platform. The amounts of visual information and of somatosensory input at the ankle were manipulated. Muscle response latencies, losses of balance, and muscle sequencing were analyzed. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
187
2
8

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(207 citation statements)
references
References 0 publications
10
187
2
8
Order By: Relevance
“…In group II a larger number of inhomogeneous graphs were recorded both with eyes open and with eyes closed, though the differences did not reach statistical significance. A decrease of articular mobility, especially at the ankle, as well as a decline of the ability to resolve sensorial information conflicts, might be the cause of these poorer results, forcing group II subjects to use an unstable strategy, 38 but these data should be confirmed in a larger series of subjects. Conversely, for the AA, IA, and AI groups, the achievement of more than 90% of homogeneous graphs during tests with the eyes open might suggest that exercise improves dynamic qualities and good control coordination.…”
Section: Discussionmentioning
confidence: 99%
“…In group II a larger number of inhomogeneous graphs were recorded both with eyes open and with eyes closed, though the differences did not reach statistical significance. A decrease of articular mobility, especially at the ankle, as well as a decline of the ability to resolve sensorial information conflicts, might be the cause of these poorer results, forcing group II subjects to use an unstable strategy, 38 but these data should be confirmed in a larger series of subjects. Conversely, for the AA, IA, and AI groups, the achievement of more than 90% of homogeneous graphs during tests with the eyes open might suggest that exercise improves dynamic qualities and good control coordination.…”
Section: Discussionmentioning
confidence: 99%
“…26 A decline in somatosensory information from the feet is a major factor in this pattern change with age. 27 Therefore the considerable impact of tai chi practice on ankle proprioception is of great benefit in the retention of balance control in old people.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of falls are the result of trips23 and serious injury due to falls is a significant problem to the aging adult. It has been suggested that falls cause more than two thirds of the accidental deaths in the over 75 age group 24. The reduction in the number of hits around the travel pathway after cataract surgery suggests that surgery may prevent trips and subsequent falls occurring.…”
Section: Discussionmentioning
confidence: 99%